Kepemimpinan Kepala Madrasah dalam melakukan Inovasi Program Pendidikan di MTs Tarbiyatus Shibyan Jadung Dungkek Sumenep - A. Tirmidzi; Ashari Ashari (Universitas Palan, 2023)
This research is a type of qualitative field research. To collect data, the methods of observation, interviews and documentation were used. Qualitative descriptive analysis is taken from facts or events and then a conclusion is drawn from the description obtained from the results, observations, interviews and documentation. The results of the research are: The leadership of the Madrasah Head in carrying out educational program innovations is going well because in the process he has implemented four educational management functions which are emphasized in the field of infrastructure, namely by carrying out planning (planning), organizing (deliberation and evaluation) carrying out motivating (mobilization). /action) and carrying out control (supervision). The planning, evaluation, motivation and supervision carried out by the head of the madrasah resulted in very significant changes and progress in improving the quality of education at MTs Tarbiyatus Shibyan, this was due to the process of innovating good education programs. So that the vision, mission and goals of the madrasah can be achieved optimally.